(untitled) (Tanzania Medical Journal, 2022)
Background Regardless of improvement in the delivery of care and treatment to patients, management of heart failure is still challenging. This is evidenced by increasing rates of both admission and readmission among patients with heart failure. Unlike medical conditions associated with heart failure such as hypertension, myocardial infection, and cardiomyopathy, this study focused on non-medical factors associated with hospital readmission among heart failure patients. Broad Objective The aim of this study was to determine non-medical factors associated with early hospital readmission among heart failure patients at Jakaya Kikwete Cardiac Institute in Tanzania. Methodology A hospital-based cross-sectional study was conducted among heart failure patients from March to May 2021 at Jakaya Kikwete Cardiac Institute, a tertiary specialized hospital in Eastern Tanzania. Data were collected using a structured questionnaire and analysis was performed using version 20 of the Statistical Package for the Social Sciences. Chi-square test and logistic regression were performed to determine associations, with a p-value of <0.05 considered for statistical significance. Results A total of 134 heart failure patients with second admission participated in this study. The mean age was 56.3 (SD 14.1), and 71 (53.0%) were females. Thirty-eight (28.4%) patients experienced early readmission (within 30 days after discharge), and non-adherence to clinic visits (AOR: 3.658; 95% CI: 1.549, 8.637; p=0.003) was associated with early readmission. Conclusion and Recommendations Heart failure is common and is associated with high rate of readmission. Non-adherence to clinic visits is an important factor leading to early hospital readmission. Strategic interventions that address non-adherence to clinic visits may be important in reducing readmissions among heart failure patients.